Hal Hal Mengasihi Sesama dan Musuh: Refleksi Dari Lukas 6:27-36 terhadap Konteks Dialog Beragama: Loving One’s Neighbor and Enemies: A Reflection on Luke 6:27–36 in the Context of Interreligious Dialogue - Andri Togatorop; Natanael Winanto; Suriawan Suriawan (Journal of Religious and Socio-Cultural, 2024)
This article discusses the concept of love within the context of Christian teachings, specifically in the relationships among people living in pluralistic societies. "Agape," the Greek term for love, represents the unconditional love that God has for humanity. This love is seen as the foundation of Jesus' teachings, emphasizing the importance of loving one’s neighbor, including one’s enemies, as a reflection of God's love. In a diverse society like Indonesia, the principle of love plays a crucial role in addressing potential religious and cultural conflicts, as differences often serve as sources of tension. Christians are called to be agents of love, not only toward fellow believers but toward all of humanity. Loving unconditionally can break down walls of hostility and prevent cycles of revenge. This article also highlights the importance of a proper understanding of love as a selfless act, demonstrated by Jesus, which inspires peace and unity within society. Through love manifested in concrete actions, Christians become reflections of God’s love in a diverse environment. Love practiced without discrimination serves as a unifying force that transcends differences in ethnicity, race, or religion and strengthens social integration to foster peace and harmony. This research contributes by emphasizing the role of unconditional love as a Christian solution for breaking down barriers of difference and conflict in plural societies, thereby promoting social harmony and peace. Artikel ini membahas konsep kasih dalam konteks ajaran Kristen, khususnya dalam relasi antara umat manusia yang hidup dalam masyarakat plural. Kasih, yang berasal dari kata Yunani "Agape," mencerminkan kasih tanpa syarat yang dimiliki Allah bagi manusia. Kasih ini dipandang sebagai dasar ajaran Yesus, yang menekankan pentingnya mengasihi sesama, termasuk musuh, sebagai cerminan kasih Allah. Dalam masyarakat yang beragam seperti Indonesia, prinsip kasih memiliki peran penting dalam mengatasi potensi konflik antaragama dan budaya, karena perbedaan sering kali menjadi pemicu ketegangan. Orang Kristen dipanggil sebagai agen kasih, tidak hanya untuk sesama umat beragama, tetapi juga bagi seluruh umat manusia. Mengasihi tanpa syarat dapat meruntuhkan tembok permusuhan dan menghindarkan balas dendam. Artikel ini juga menyoroti pentingnya pemahaman yang benar akan kasih sebagai suatu tindakan tanpa pamrih yang ditunjukkan Yesus, yang menginspirasi perdamaian dan persatuan dalam masyarakat. Melalui kasih yang diwujudkan dalam tindakan nyata, orang Kristen menjadi cerminan kasih Allah dalam lingkungan masyarakat yang majemuk. Kasih, yang dijalankan tanpa diskriminasi, berfungsi sebagai kekuatan pemersatu yang melampaui perbedaan suku, ras, atau agama, serta memperkokoh integrasi sosial demi mewujudkan kedamaian dan kerukunan hidup. Penelitian ini memberikan kontribusi dengan menekankan peran kasih tanpa syarat sebagai solusi Kristen untuk meruntuhkan sekat-sekat perbedaan dan konflik dalam masyarakat plural, guna mewujudkan perdamaian dan kerukunan sosial.